Aulacoseira veraluciae sp. nov. (Coscinodiscophyceae, Aulacoseiraceae): a common freshwater diatom from Brazil - Tremarin, Priscila Izabel; Ludwig, Thelma; Torgan, Lezilda (Phytotaxa, 2014)
Examination of samples from different aquatic environments from Brazil revealed the presence of a new Aulacoseira species. Aulacoseira veraluciae Tremarin, Torgan & T. Ludwig is described and illustrated with light and scanning electron microscopy, and its morphology compared with that of similar species, such as A. muzzanensis (Meister) Krammer, A. granulata (Ehrenberg) Simonsen and A. agassizii (Ostenfeld) Simonsen. The new species is characterized mainly by the straight pervalvar rows of areolae, morphology of the linking spines, shape and position of the rimoportulae on the valve mantle, deepness and thickness of the ringleiste.